2008
DOI: 10.1007/s10886-008-9568-2
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for the Induction of Brown Algal Chemical Defense by the Phytohormones Jasmonic Acid and Methyl Jasmonate

Abstract: Induced chemical defense reactions are widespread in marine brown algae. Despite the evidence that the biosynthesis of defense metabolites can be up-regulated upon herbivory, we do not know how this regulation of biosynthetic pathways to secondary metabolites is achieved in brown algae. In higher plants, the phytohormone jasmonic acid (JA) is crucial for the mediation of induced chemical defenses, and several findings of this metabolite from marine sources have been reported. We tested the hypothesis that JA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…In comparison, plants with these studies, Wiesemeier et al (2008) did not observe defense-related effects of jasmonate in other species of brown algae.…”
Section: Introductioncontrasting
confidence: 58%
“…In comparison, plants with these studies, Wiesemeier et al (2008) did not observe defense-related effects of jasmonate in other species of brown algae.…”
Section: Introductioncontrasting
confidence: 58%
“…Gao et al (2012a) also reported that JA was an effective regulator that stimulated astaxanthin production in H. pluvialis. However, it appeared to play no role in brown algae for defense induction (Wiesemeier et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have indicated that algae experiencing increased abiotic stresses are less likely to produce chemical deterrents (Renaud et al. 1990, Wiesemeier et al. 2008).…”
Section: Discussionmentioning
confidence: 99%